Impact of 1-methylcyclopropene and controlled atmosphere storage on polyamine and 4-aminobutyrate levels in “Empire” apple fruit - Deyman, Kristen L.; Brikis, Carolyne J.; Bozzo, Gale G.; Shelp, Barry J. (Frontiers in Plant Science, 2014)
1-Methylcyclopropene (1-MCP) delays ethylene-meditated ripening of apple (Malus domestica Borkh.) fruit during controlled atmosphere (CA) storage. Here, we tested the hypothesis that 1-MCP and CA storage enhances the levels of polyamines (PAs) and 4-aminobutyrate (GABA) in apple fruit. A 46-week experiment was conducted with “Empire” apple using a split-plot design with four treatment replicates and 3°C, 2.5 kPa O2, and 0.03 or 2.5 kPa CO2 with or without 1 μL L-1 1-MCP. Total PA levels were not elevated by the 1-MCP treatment. Examination of the individual PAs revealed that: (i) total putrescine levels tended to be lower with 1-MCP regardless of the CO2 level, and while this was mostly at the expense of free putrescine, large transient increases in soluble conjugated putrescine were also evident; (ii) total spermidine levels tended to be lower with 1-MCP, particularly at 2.5 kPa CO2, and this was mostly at the expense of soluble conjugated spermidine; (iii) total spermine levels at 2.5 kPa CO2 tended to be lower with 1-MCP, and this was mostly at the expense of both soluble and insoluble conjugated spermine; and (iv) total spermidine and spermine levels at 0.03 kPa were relatively unaffected, compared to 2.5 kPa CO2, but transient increases in free spermidine and spermine were evident. These findings might be due to changes in the conversion of putrescine into higher PAs and the interconversion of free and conjugated forms in apple fruit, rather than altered S-adenosylmethionine availability. Regardless of 1-MCP and CO2 treatments, the availability of glutamate showed a transient peak initially, probably due to protein degradation, and this was followed by a steady decline over the remainder of the storage period which coincided with linear accumulation of GABA. This pattern has been attributed to the stimulation of glutamate decarboxylase activity and inhibition of GABA catabolism, rather than a contribution of PAs to GABA production.